2020
DOI: 10.1002/cbin.11306
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐643 inhibits lipopolysaccharide‐induced endometritis progression by targeting TRAF6

Abstract: Endometritis is a prevalent disease with inflammation of uterus endangering women reproductive health. MicroRNAs (miRNAs) play important roles in inflammatory disorders, including endometritis. However, the role and mechanism of miR‐643 in endometritis development remain unclear. This study aimed to investigate the effect of miR‐643 on lipopolysaccharide (LPS)‐induced inflammatory response and clarify the potential mechanism. LPS‐treated human endometrial epithelial cells (HEECs) were cultured to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Evidences also confirmed that miR-146b-5p is tumor suppressor by inhibiting the TRAF6/p-Akt signaling pathway in vitro and in vivo [77]. miR-643 has recently been proved to targeting TRAF6 in human endometrial epithelial cells (HEECs) that significantly reduces the expression of TRAF6 [78]. miR-124 has also been reported to be related to negative regulation of TRAF6 expression in human osteosarcoma cells and colorectal cancer cells [79,80].…”
Section: The Regulation Of Traf6 By Expressionmentioning
confidence: 81%
“…Evidences also confirmed that miR-146b-5p is tumor suppressor by inhibiting the TRAF6/p-Akt signaling pathway in vitro and in vivo [77]. miR-643 has recently been proved to targeting TRAF6 in human endometrial epithelial cells (HEECs) that significantly reduces the expression of TRAF6 [78]. miR-124 has also been reported to be related to negative regulation of TRAF6 expression in human osteosarcoma cells and colorectal cancer cells [79,80].…”
Section: The Regulation Of Traf6 By Expressionmentioning
confidence: 81%
“…90 Studies revealed that miR-643 expression is reduced in lipopolysaccharide-induced endometritis and a high level of miR-643 expression reduces inflammation in those tissues. 86 The lower level of miR-488 expression in lipopolysaccharide induces inflammation of the endometrium. On the other hand, this miRNA suppresses inflammatory cytokines production in BEND cells.…”
Section: Pelvic Inflammatory Diseasementioning
confidence: 99%
“…Also, TRAF6, a validated target of miR-643 and TRAF6 restoration, reversed the effects of miR-643 on inflammation response in LPS-treated human endometrial epithelial cells. Collectively, miR-643 attenuated LPS-induced inflammatory response by targeting TRAF6, indicating a novel avenue for treating CE (156).…”
Section: Biochemical Variationsmentioning
confidence: 94%